Enriching college students through study abroad: a case of Nepal Field Experience - Part 3 - D., Durga; Corwin, Hali; Eddings, Katie; Bailey, George; Braun, Andrew; Mann, Aubrey; Gomez, Victoria; Heafner, Holly; Faulk, William; Immel, Luke; et al. (Scientific Journal of Bielsko-Biala School of Finance and Law, 2020)
With a view of providing an unsurpassed opportunity to college students, who are mostly from Louisiana, in gaining a comprehensive understanding of Global Climate Change issues, we completed the first Nepal Field Experience Pilot Study Abroad from May 21-June 8, 2019. A total of fifteen students from the University of Louisiana at Lafayette, Louisiana, USA, and one graduate student from University of Arizona, Arizona, USA, participated in the program. Students examined and documented the effects of climate change impacts on agriculture, water resources, wildlife, local communities, forest resources, and other ecological and environmental settings of the country. They identified various climate change mitigation and adaptation measures that had been implemented and noted gaps between policy measures and ground realities. Research topics selected by the students included the following: climate change impacts on wildlife, water pollution, structural geology of Nepal, changing rainfall patterns and adaptation, climate change and agricultural production, geology of Kathmandu valley, air quality of Kathmandu valley, changing hydrology of glaciated landscape, climate change and geohazards, emerging diseases and pests on agricultural crops, climate change adaptation by local communities, green infrastructure and climate-smart technologies, climate change impact on drinking water sources, the roadside geology, and emerging diseases, parasites and zoonotics. Each student completed their individual research project, synthesized the results, and presented to local stakeholders in conference organized by a nonprofit nongovernmental organization, Asta-Ja Rsearch and Development Center (Asta-Ja RDC), Kathmandu, Nepal. Findings of the study reveal that Nepal is experiencing huge impacts of climate change in multiple fronts including atmospheric conditions and snowfall, temperature rise, occurrence of droughts and flooding, changes on monsoon pattern, emerging diseases and pests on crops and livestock, and declining drinking water sources. Environmental pollution, especially the air and water pollution and waste management, was very serious affecting public health, aesthetics, and even the tourism of the country. In order to reverse environmental degradation and enhance climate change adaptation, immediate implementation of effective, comprehensive, coordinated, and well-thought-out climate change adaptation and environmental initiatives are necessary. Nepal Field Experience was a lifetime learning experience for the students.